PENDAMPINGAN PENINGKATAN KUALITAS SENI MEMBACA AL-QUR’AN PADA SISWA TAMAN PENDIDIKAN AL-QUR’AN - Wardatus Syarifah (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
The community of Pakamban Daya Village, Sumenep is an example of a community that highly values religious knowledge, this can be seen from the many Islamic boarding schools or Taman Pendidikan AL-Qur’an (TPQ) there. One of the religious learning processes at TPQ is reading the Al-Qur'an. Reading will support learning activities carried out both in class and at Islamic boarding schools. Learning to read the Al-Qur'an basically must pay attention to the main principles that every teacher needs to understand. This is because learning to read the Al-Qur'an is of course different from learning to read books, novels or other reading materials. The art of reading the Al-Qur'an is the tilawati method, where the method of learning to read the Al-Qur'an is with the basic technique of talqin-taqlid (imitation) as the Prophet Muhammad imitated the reading of the Angel Jibril. Thus, this service is carried out to help TPQ students read the Al-Qur'an with good and correct tilawati as an effort to improve the quality of the art of reading the Al-Qur'an. The program was held at the Pakamban Daya village hall with various strategies that had been implemented and received full support from the village head, village officials and the local community. This service is carried out as a form of the Tri Dharma of college, namely providing community service.